Bridging the gap: awareness of Muslim friendly tourism and hospitality assurance and recognition (MFAR) in Pagoh edu hub - Herry Izi, Farisya Arina; Md Sawari, Siti Salwa; Abas, Siti Aisah (Korint Yayincilik, 2025)
Muslim friendly tourism is expanding globally, with Malaysia positioning itself as a leader through initiatives like the Muslim friendly Tourism and Hospitality Assurance and Recognition (MFAR) certificate. However, awareness of MFAR remains limited at the community level, particularly within educational hubs such as Pagoh Edu Hub. This study aims to assess the level of MFAR awareness among students, staff, and local entrepreneurs in Pagoh and to explore strategies for promoting Muslim-friendly tourism practices. A mixed-methods approach was used, combining quantitative surveys (n=162) and qualitative interviews (n=15) across institutions such as IIUM, UTHM, and local SMEs. Findings reveal a significant gap in MFAR awareness only 25% of respondents recognized the MFAR logo despite widespread support for halal and Shariah-compliant tourism features. Over 90% valued halal-certified food, prayer facilities, and Muslim-friendly accommodations in travel decisions. The study highlights a disconnect between community values and formal tourism recognition schemes. It recommends targeted awareness campaigns, stakeholder engagement, and educational outreach to improve MFAR visibility. These efforts are critical for advancing inclusive tourism, aligning with Malaysia’s halal tourism agenda, and enhancing socio-economic opportunities in local communities.